WEB-BASED PAYROLL SYSTEM DEVELOPMENT USING THE PROTOTYPING METHOD AND STRUCTURED DATABASE DESIGN - Felix Tandrio; Melissa Indah Fianty (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2026)
Effective payroll management is essential for accurate salary calculations and efficient financial operations. Many companies, including beverage distribution firms, still rely on spreadsheet-based payroll systems using Microsoft Excel. While Excel provides computational flexibility, it requires extensive human intervention, making it a semi-manual process prone to errors, data inconsistency, and limited scalability. This study develops a web-based payroll information system using a structured workflow that combines the Prototyping method and the Database System Development Life Cycle (DSDLC). Methodology includes business process analysis with the 5W+1H approach, database design using UML, normalization, SQL implementation, and user interface development based on the KISS principle. The system was implemented with MySQL and PHP/Laravel. Evaluation through User Acceptance Testing (UAT) with payroll administrators and HR staff yielded a satisfaction score of 90.8% (Highly Eligible). The successful implementation demonstrates enhanced payroll efficiency, data integrity, and user accessibility. The system shows potential for scalability and future improvements, including cloud integration, advanced security, and financial system connectivity.